SDG3 sustainable development model for Chinese ethnic intangible cultural heritage sports projects: a quantitative study - Fu, Jiangping; Li, Hua; Yu, Yi; Yue, Ninggang; Zhang, Weiping; Zhou, Tian (Frontiers in Sports and Active Living, 2025)
ObjectiveBackground: The World Intellectual Property Organization (WIPO) 2022 report emphasizes that 75% of intangible cultural heritage projects worldwide face the “modernization trap”, with the intensity of risk positively correlated with the degree of commercialization of the project. Sports projects should avoid this concrete phenomenon. The sustainable development of China's ethnic intangible cultural heritage sports projects must be based on a comprehensive/integrated model that encompasses sports culture (culture, economy, society, and resources).MethodUsing integrated model theory, a sustainable development model was created. A group of 10 experts was established, and data was obtained through two rounds of questionnaires administered to the expert group. Through sports culture theory, combined with the EGG model (aggregation model), identify risk factors for safety accidents, identify risk factors for the lack of sports culture (intangible cultural heritage), and identify the relationship between the two types of risks. Based on a multi-subject collaboration mechanism, the Decision-Making Trial and Evaluation Laboratory (DEMATEL) is incorporated as a multi-criteria decision-making method to calculate the prominence and correlation of influencing factors and assess the degree of impact of risk factors.ResultsA fault tree analysis of 54 indicators (risk factors) was conducted to determine a model for the sustainable development of intangible cultural heritage sports projects (EGG), including 5 first-level indicators, 11 s-level indicators, and 38 third-level indicators. The most prominent and influential factors (risk factors) that have been identified include five third-level indicators and one first-level indicator. Risks level-3 indicators) are divided into 5 major prominent causes/factors (T5, T6, T17, T23, and T34), and 4 major related causes/factors (T3, T7, T20, T33, and T36). The F5 intangible cultural heritage (sports) dimension, as an important dimension of the sustainable development model (representing well-being), was observed (third prominent indicator, not last place; the lowest related causes/factors; sustainable well-being is not yet apparent).ConclusionThe results indicate that quantitative (calculation) integrated models are scientific and reliable tools, which can be used to reduce the risk assessment of sustainable development in Chinese ethnic intangible cultural heritage sports projects.